TÍTULO: O ENSINO DE LÍNGUAS E A RESSIGNIFICAÇÃO DA PRÁTICA DOCENTE - MACAGNAN, MARIA J.; ASSUMPÇÃO, MONE S. P. D.; SILVA, FABIANA D. K. D.; KIESLICH, JACI; LANG, MARISTELA R.; NONEMACHER, TANEA; SANTOS, ROSITA D. S. (Salão do Conhecimento, 2013)
Resumo